Tree water dynamics in a drying and warming world. (20th June 2017) - Grossiord, Charlotte; Sevanto, Sanna; Borrego, Isaac; Chan, Allison M.; Collins, Adam D.; Dickman, Lee T.; Hudson, Patrick J.; McBranch, Natalie; Michaletz, Sean T.; Pockman, William T.; Ryan, Max; Vilagrosa, Alberto; et al.
Abstract: Disentangling the relative impacts of precipitation reduction and vapour pressure deficit ( VPD ) on plant water dynamics and determining whether acclimation may influence these patterns in the future is an important challenge. Here, we report sap flux density ( F D ), stomatal conductance ( G s ), hydraulic conductivity ( K L ) and xylem anatomy in piñon pine ( Pinus edulis ) and juniper ( Juniperus monosperma ) trees subjected to five years of precipitation reduction, atmospheric warming (elevated VPD ) and their combined effects. No acclimation occurred under precipitation reduction: lower G s and F D were found for both species compared to ambient conditions. Warming reduced the sensibility of stomata to VPD for both species but resulted in the maintenance of G s and F D to ambient levels only for piñon. For juniper, reduced soil moisture under warming negated benefits of stomatal adjustments and resulted in reduced F D, G s and K L . Although reduced stomatal sensitivity to VPD also occurred under combined stresses, reductions in G s, F D and K L took place to similar levels as under single stresses for both species. Our results show that stomatal conductance adjustments to high VPD could minimize but not entirely prevent additive effects of warming and drying on water use and carbon acquisition of trees in semi‐arid regions. Abstract : Membrane lipid remodelling is a metabolic adaptation that replaces membrane phospholipids by non‐phosphorous galactolipids, thereby allowing phosphate‐starved plants to obtain scarce phosphate yet maintain the membrane structure. Here, we stimulated de novo phospholipid biosynthesis by overexpressing lysophosphatidic acid acyltransferase 2 (LPAT2) in Arabidopsis, and indeed increased root length specifically under phosphate starvation with no effect on phosphate starvation response. The findings propose a revised model of membrane lipid remodelling, in which de novo phospholipid biosynthesis mediated by LPAT2 contributes significantly to root development under phosphate starvation.